Relapsed/refractory diffuse large B cell lymphoma with cardiac involvement: A case report and literature review - Yang, Yuanyuan; Li, Zixuan; Li, Yuntao; Zhao, Yue; Shi, Mingxia (Frontiers in Oncology, 2023)
Background: Hematological malignancies of the heart (CHMs) are extremely rare, and include leukemia, lymphoma infiltration, and multiple myeloma with extramedullary manifestations. Cardiac lymphoma can be divided into primary cardiac lymphoma (PCL) and secondary cardiac lymphoma (SCL). Compared to PCL, SCL is relatively more common. Histologically, the most frequent SCL is diffuse large B-cell lymphoma (DLBCL). The prognosis of lymphoma in patients with cardiac involvement is extremely poor. CAR T-cell immunotherapy has been recently become a highly effective treatment for relapsed or refractory diffuse large B-cell lymphoma. To date, there are no guidelines that provide a clear consensus on the management of patients with secondary heart or pericardial involvement. We report a case of relapsed/refractory DLBCL that secondarily affected the heart. Case presentation: A male patient was diagnosed with double-expressor DLBCL based on biopsies of mediastinal and peripancreatic masses and fluorescence in situ hybridization. The patient received first-line chemotherapy and anti-CD19 CAR T cell immunotherapy, but developed heart metastases after 12 months. Considering his physical condition and economic situation of the patient, two cycles of multiline chemotherapies were administered, followed by CAR-NK cell immunotherapy and allogeneic hematopoietic stem cell transplantation (allo-HSCT) at another hospital. After achieving a six-month survival, the patient died of severe pneumonia. Conclusion: The response of our patient emphasizes the importance of early diagnosis and timely treatment to improve the prognosis of SCL and serves as an important reference for SCL treatment strategies.